Teaching Coping Skills to Adolescents with Learning Problems. - Silverman, Rita; Zigmond, Naomi; Sansome, Jan (Focus on Exceptional Children, 1981)
The article focuses on the development of School Survival Skills Curriculum as an integral part of any comprehensive program to serve secondary school-age students with learning and behavior problems in the U.S. The Curriculum's purpose is to prepare students to deal effectively with demands of the secondary school environment and the world beyond school. It is divided into three strands of activities (Behavior Control strand, Teacher Pleasing Behavior, and Study Skills), each of this strands is focusing on a set of skills that seems to be lacking in high school students with learning problems. The curriculum is considered to be mastered only after the students demonstrated the competencies in their content area classes. By installing such a curriculum for secondary students with learning disabilities is a way to facilitate integration of these students into mainstream education.